The Role of Sharia The Role Of Sharia Financial Literacy In Millennials' Adoption Of Islamic Financial Products At BMT Nu Besuki: Implications For Islamic Financial Inclusion - Mohammad Alief Hidayatullah; Siti Sofiatun (CV Putra Publisher, 2026)
This study aims to analyze the role of Islamic financial literacy in influencing millennials' decisions to use Islamic financial products at BM T NU Besuki. The rapid development of Islamic financial institutions in Indonesia has not been fully supported by an adequate level of Islamic financial literacy, particularly among the millennial generation. This research employs a quantitative approach with a descriptive-correlational design. The population consists of millennial customers aged 25–40 years who are active members of BMT NU Besuki. Using purposive sampling technique, 75 respondents were selected as the research sample. Data were collected through a structured questionnaire based on a Likert scale and analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The findings indicate that Islamic financial literacy has a positive and significant effect on the decision to use Islamic financial products. The higher the level of Islamic financial literacy, the stronger the tendency of millennials to choose and utilize sharia-based financial services. These results highlight the importance of strengthening Islamic financial literacy programs as a strategic effort to enhance product utilization and promote ethical financial behavior among millennials.